A Polyketide Synthase Component for Oxygen Insertion into Polyketide Backbones. Issue 36 (31st July 2018) - Meoded, Roy A.; Ueoka, Reiko; Helfrich, Eric J. N.; Jensen, Katja; Magnus, Nancy; Piechulla, Birgit; Piel, Jörn
Abstract: Enzymatic core components from trans ‐acyltransferase polyketide synthases (trans‐AT PKSs) catalyze exceptionally diverse biosynthetic transformations to generate structurally complex bioactive compounds. Here we focus on a group of oxygenases identified in various trans‐AT PKS pathways, including those for pederin, oocydins, and toblerols. Using the oocydin pathway homologue (OocK) from Serratia plymuthica 4Rx13 and N ‐acetylcysteamine (SNAC) thioesters as test surrogates for acyl carrier protein (ACP)‐tethered intermediates, we show that the enzyme inserts oxygen into β‐ketoacyl moieties to yield malonyl ester SNAC products. Based on these data and the identification of a non‐hydrolyzed oocydin congener with retained ester moiety, we propose a unified biosynthetic pathway of oocydins, haterumalides, and biselides. By providing access to internal ester, carboxylate pseudostarter, and terminal hydroxyl functions, oxygen insertion into polyketide backbones greatly expands the biosynthetic scope of PKSs. Abstract : Puts the O in backb‐O‐ne : Modular polyketide synthases (PKSs) are functionally complex enzymes that generate diverse bioactive natural products with contiguous carbon chains. A PKS core component was identified that catalyzes oxygen insertion into the growing polyketide backbone by Baeyer–Villiger oxidation to give diverse noncanonical structural features.